개방형 산란계사의 암모니아 배출계수 개발을 위한 추적가스법 적용 연구 - 강성민(Kang, Seong Min); 노준영(Rho, Joon Young); 김고은(Kim, Go Eun); 전의찬(Jeon, Eui-Chan) (한국기후변화학회지, 2022)
Ammonia is one of the precursors for secondary generation of PM-2.5 and is one of the important factors in PM-2.5 management. The livestock sector is the main source of ammonia emission in Korea; except for cattle and pigs, overseas emission factors are used. In Korea, research on the development of emission factors in the livestock sector has been mainly conducted using the chamber method, but this method has disadvantages in that it is difficult to consider the actual ventilation amount in the livestock house and it is not possible to monitor ammonia emission in real-time. In this study, the applicability of the tracer gas method used abroad was investigated to compensate for these shortcomings. The experiment was conducted for open-type laying hens and was performed according to the Vera test protocol, an overseas standard. The tracer gas method showed no significant difference in domestic and overseas emission factors, so it is judged that the tracer gas method can be fully utilized. Therefore, in this study, NH3 emission factors have been developed by methods other than the chamber method mainly used in livestock houses. It is necessary to apply and verify this method in more places in the future, and it is judged that it is necessary to conduct research on other livestock as well. KCI Citation Count: 0